Texts, Lies, and Mediascapes: Communication Technologies and Social Media as Risk in the Educational Landscape - Pelkey, Samuel; Stelmach, Bonnie; Hunter, Darryl (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
Studies have shown how digital communications impact administrators’ work, but few have looked at the reputational risks to school administrators incurred through social media and digital communications. This Alberta case study looks at risk through Kasperson et. al’s (1988) social amplification of risk framework for an exclusion room controversy. Twitter responses are analyzed and interpreted over a longitudinal, 5-year period. Despite school administrators’ perceptions that risk might be generated on social media from community-led, grass-roots sources, traditional figures and agencies such as provincial news media and politicians appear more influential than school administrators, teachers, or parents in the Twitterverse. Implications are drawn for educational administrative behaviour and policy.